Fetal health anxiety: development and psychometric properties of the fetal health anxiety inventory - Sarah J. Reiser; Kristi D. Wright (Taylor & Francis Group, 2019)
Objective: To develop a measure to assess fetal health anxiety and examine its factor structure, convergent and divergent validity. Methods: In Study 1, the Short Health Anxiety Inventory-14 item version (SHAI) (Salkovskis et al., Psychol Med. 2002;32:843-853) was adapted for use with pregnant women to examine fetal health anxiety named the Fetal Health Anxiety Inventory (FHAI). Four pregnant women and three subject matter experts (SMEs) reviewed the FHAI. In Study 2, 100 pregnant women completed the FHAI and related self-report measures. Results: In Study 1, both reviewer groups provided feedback directing minor changes to the FHAI. In Study 2, a revised version was used. The revised FHAI demonstrated excellent internal consistency (α = 0.91). Results from an EFA suggested that the FHAI may be conceptualized as a one- or two-factor scale. Convergent (pregnancy-related anxiety [r = 0.56, p = .0001], parental health anxiety [r = 0.53, p = .0001], anxiety [r = 0.57, p = .0001], anxiety sensitivity [r = 0.28, p = .004] and intolerance of uncertainty [r = 0.29, p = .003]) and divergent (parental depression [r = 0.16, p = .12]) validity was evidenced with additional measures of interest. Conclusion: Preliminary findings suggest that the FHAI represents a psychometrically sound instrument to measure the construct of fetal health anxiety. Practical and theoretical implications of the present results are discussed.